2019
DOI: 10.1186/s13063-019-3255-1
|View full text |Cite|
|
Sign up to set email alerts
|

An individualised versus a conventional pneumoperitoneum pressure strategy during colorectal laparoscopic surgery: rationale and study protocol for a multicentre randomised clinical study

Abstract: Background A recent study shows that a multifaceted strategy using an individualised intra-abdominal pressure titration strategy during colorectal laparoscopic surgery results in an acceptable workspace at low intra-abdominal pressure in most patients. The multifaceted strategy, focused on lower to individualised intra-abdominal pressures, includes prestretching the abdominal wall during initial insufflation, deep neuromuscular blockade, low tidal volume ventilation settings and a modified lithoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…28,29 Perhaps rather than comparing depth of neuromuscular block or assigned intra-abdominal pressure, future studies may investigate an individualised vs conventional (static) approach to insufflation pressure. 30 We found no difference in DASAIM scores, time to PACU discharge, or postoperative nausea between the two treatment groups. Similarly, there were no differences in POMS scores or hospital LOS.…”
Section: Discussionmentioning
confidence: 51%
“…28,29 Perhaps rather than comparing depth of neuromuscular block or assigned intra-abdominal pressure, future studies may investigate an individualised vs conventional (static) approach to insufflation pressure. 30 We found no difference in DASAIM scores, time to PACU discharge, or postoperative nausea between the two treatment groups. Similarly, there were no differences in POMS scores or hospital LOS.…”
Section: Discussionmentioning
confidence: 51%
“…It is possible that deep neuromuscular blockade is not required for adequate vision in low IAP laparoscopic colorectal surgery, however safety concerns have also led other similar studies and trials to combine low IAP and deep neuromuscular blockade in laparoscopic colorectal surgey. 28,29 Although statistical significance was not achieved for the key outcome of this study, deep neuromuscular block was observed to be potentially advantageous for several of the factors examined. There may be less inflammation associated with deep neuromuscular blockade as the CRP was observed to be lower on day 1 which persisted out to day 3.…”
Section: Discussionmentioning
confidence: 65%
“…Written informed consent was obtained from all subjects before entering the trial. The study was registered before patient enrolment at EudraCT (study 2016‐001693‐15) and http://clinicaltrials.gov (NCT02773173), and the protocol was prepublished 13 and updated 14 .…”
Section: Methodsmentioning
confidence: 99%
“…PQRS scores were also analysed as ordinal variables 13 . With this approach there is no dichotomization of PQRS outcomes, and scores are treated as variables in ordered categories.…”
Section: Methodsmentioning
confidence: 99%